Odpowiedź :
Odpowiedź:
c) (2 x - 1)³ -4 x*(2 x - 1)*( x + 2) > 0
( 2 x - 1)*[( 2 x - 1)² - 4 x *( x + 2)] > 0
( 2 x -1)*[ 4 x² - 4 x + 1) - 4 x² - 8 x] > 0
(2 x - 1)*[ - 12 x + 1 ] > 0
2*( x - 0,5)* [ -12*( x - [tex]\frac{1}{12}[/tex] )] >0
- 24*( x - 0,5)*( x - [tex]\frac{1}{12}[/tex] ) > 0
x1 = [tex]\frac{1}{12}[/tex] x2 = [tex]\frac{1}{2}[/tex]
a = - 24 < 0 - ramiona paraboli są skierowane do dołu, wiec
x ∈ ( [tex]\frac{1}{12}[/tex] ; [tex]\frac{1}{2}[/tex] )
===============
d) [tex]\frac{( x - 2)^3}{2}[/tex] - [tex]\frac{(x - 1)*( x^2 + x + 1)}{3}[/tex] ≤ [tex]\frac{1}{6}[/tex] x³ - [tex]\frac{2}{3}[/tex] / * 6
3*( x - 2)³ - 2*( x -1)*(x² + x + 1) ≤ x³ - 4
3*(x³ - 6 x² + 12 x - 8) - (2 x - 2)*( x² + x + 1) ≤ x³ - 4
3 x³ - 18 x² + 36 x -24 - ( 2 x³ + 2 x² + 2 x -2 x² -2 x -2 ) ≤ x³ - 4
- 18 x² + 36 x - 18 ≤ 0 / : 18
- x² +2 x - 1 ≤ 0
- ( x - 1)² ≤ 0
x ∈ R = ( - ∞ ; +∞ )
===================
Szczegółowe wyjaśnienie: